The Entropy Production—as Cornerstone in Applied Nonequilibrium Thermodynamics (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
With this Special Issue, we hope to encourage a large efforts in this important field. The purpose of the Special Issue is to demonstrate the strength and importance of the theory of nonequilibrium thermodynamics, with its fundamental basis in entropy production, when used to improve the understanding of processes essential to mankind, industry, or nature at large. The topics cover fundamental aspects and applications of all sorts, for instance the applications that Signe Kjelstrup worked on: fuel cells, batteries, thermoelectric devices, chemical reactors, distillation columns, and reindeer or seal noses.